Effect of replacement of concentrate feed with Moringa leaves on dietary nutrient utilization of non-descript Chhattisgarh goats - Prusty, Sonali; Tiwari, Sita prasad; gendley, manoj kumar; krishnan, kundan; Dubey, Meenu; Parveen, Kaiser; Doneria, Raina; Gade, Nitin (Indian Journal of Dairy Science, 2023)
An experiment was conducted to analyse the effect of replacing commercially available concentrate mixture with driedÂ  Moringa oleifera leaves on the nutrient utilization pattern of diet in non-descript goat breeds of Chhattisgarh. Eight non-descript yearling goats allotted randomly into 2 groups (group1 and group2) based on their BW (13.48Â±1.07 kg). Animals in group 1 were offered concentrate @ 1.5% of body weight and hybrid napier grass ad lib. In the group 2, 50% of concentrate was replaced by Moringa leaves on dry matter basis. Dried leaves were analyzed for their chemical composition. CP content was 27.52% whereas, Ca, P, Fe and Zn were 3.2%, 2.5%. 125.4 ppm and 29.8 ppm, respectively. There was no significant effect on palatability of feed that was evident from similar DM intake in both the groups. Intake of individual nutrients also did not differ significantly among the groups. There was no effect of moringa leaves inclusion on the nutrient utilization pattern as the digestibility of nutrients were similar in either groups. However significantly higher N retention was observed in Moringa supplemented group compared to commercial concentrate supplemented group. Thus, Moringa supplementation was helpful in reducing the quantity of commercial concentrate mixture inclusion in the diet of non-descript goats.